2007
DOI: 10.1103/physrevd.76.054007
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid and pseudo-Goldstone modes in three flavor crystalline color superconductivity

Abstract: We study the bosonic excitations in the favorite cubic three flavor crystalline LOFF phases of QCD. We calculate in the Ginzburg-Landau approximation the masses of the eight pseudo NambuGoldstone Bosons (NGB) present in the low energy theory. We also compute the decay constants of the massless NGB Goldstones associated to superfluidity as well as those of the eight pseudo NGB. Differently from the corresponding situation in the Color-Flavor-Locking phase, we find that meson condensation phases are not expected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…This has been corrected later [73] and revealed that two-flavor color-superconducting LOFF phases can be energetically favored in compact stars and form stable hybrid star configurations with masses above 2 M ⊙ [74,75]. The crystallinity of the 2SC phase may not essentially affect the question for the maximum mass of hybrid stars but can affect their cooling behavior and therefore our understanding of NS phenomenology [76].…”
Section: Dense Hybrid Star Mattermentioning
confidence: 99%
“…This has been corrected later [73] and revealed that two-flavor color-superconducting LOFF phases can be energetically favored in compact stars and form stable hybrid star configurations with masses above 2 M ⊙ [74,75]. The crystallinity of the 2SC phase may not essentially affect the question for the maximum mass of hybrid stars but can affect their cooling behavior and therefore our understanding of NS phenomenology [76].…”
Section: Dense Hybrid Star Mattermentioning
confidence: 99%
“…Here we shall focus on the microscopic derivation of the H−phonon Lagrangian and introduce it by means of the transformation ψ → U † ψ with U = exp {iϕ/f ϕ }, where f ϕ is its decay constant. Taking into account the unitary rotations, the HDET Lagrangian takes the form (Anglani et al, 2007)…”
Section: Goldstone Modesmentioning
confidence: 99%
“…Treating both the quark-quark and the quark-antiquark interaction in a meanfield approximation, and minimizing the free energy with respect to the chiral (< i//i// >) and the diquark (< i//i// >) condensates, it is possible to obtain the ^-dependence of the constituent masses of the quarks, where ji is the average chemical potential of the three flavors. In the case of three flavor crystalhne LOFF phases [22] the color gauge group is again spontaneously broken, so the eight gluons acquire mass by the Anderson-Higgs mechanism, but the presence of nonzero quark masses in the Lagrangian and the difference in chemical potential between the flavors give rise to eight Goldstone modes corresponding to the SU(3)^ breaking. 2 (right panel).…”
Section: Three Flavor Crystalline Phasesmentioning
confidence: 99%
“…The corresponding plot is presented in Fig. In [22] the masses and the decay constants for these nine mesons are computed, using a Ginzburg-Landau expansion of the quark propagator up to the second power of A/5^. Taking in particular the values for the strange quark constituent mass (the constituent masses of up and down quarks are basically the same as their current masses in the region of interest, since the corresponding chiral symmetry has already been restored), and putting them in the window (5), it is possible to directly obtain the range of ji where the crystalhne LOFF phases are favored.…”
Section: Three Flavor Crystalline Phasesmentioning
confidence: 99%